Creating Child-Friendly Schools in Islamic Educational Institutions in East Kalimantan for Continuous Strengthening of Student Characters - Sultani; Ilyasin, Mukhamad; Robingatin (The Indonesian Institute of Science and Technology Research, 2025)
Children's education plays a crucial role in shaping the character and morals of the next generation. A child-friendly environment in Islamic educational units is an urgent need to support the holistic development of children physically, emotionally, and psychologically. Integrating Islamic Religious Education (IRE) in the education system strengthens spiritual, moral, and social values, thus creating individuals who are ethical and responsible. This study uses a descriptive qualitative method with a case study approach at MAN Bontang and MTsN Model Samarinda (both are public Islamic-based schools). Data were collected through interviews, observations, and documentation with purposive sampling techniques involving the head of the madrasah, IRE teachers, parents of students, and students. Data analysis was done through data reduction, presentation, and inductive conclusion drawing. The study results showed that the child-friendly environment in both madrasahs contributed to strengthening students' character based on sustainability. MAN Bontang emphasized coastal ecosystems and social entrepreneurship, while the MTsN Model Samarinda prioritized environmental education and zero bullying policies. The main supporting factors were madrasah policies that supported character education, community participation, and adequate facilities and infrastructure. This study also concluded that implementing a child-friendly environment in madrasas can create an educational ecosystem oriented towards academics and character formation based on sustainability. Synergy between schools, communities, and governments is needed to strengthen character education implementation sustainably.